Analysis of Abortion Cases Data at the Referral Hospital of Haho Health District, Notsè – Togo, 2012 – 2017 - Agballa Mébiny-Essoh Tchalla Abalo; Essona Matatom Akara; Hamadi Assane; Degnanou Komi; Edem Kpeglo; Bernard Sawadogo; Simon Antara (Journal of Interventional Epidemiology and Public Health)
Introduction: More than 95 percent of unsafe abortions occur in developing countries and contribute to 4.70 percent to 13.20 percent of maternal deaths. Abortions’ magnitude and characteristics are unknown at Notsè hospital yet these parameters are critical for effective planning of interventions and to mobilize resources for abortion management. We aimed to describe data quality, socio-demographic and clinical features of abortions cases.